Battery thermal management for microchannel cooling system with scanning flow method - Qin, Qing; Luo, Zhenhua; Luk, Patrick Chi-Kwong (Institute of Electrical and Electronics Engineers (IEEE), 2025)
The demand for high-performance electric vehicles has rapidly increased, necessitating rapid charging and efficient thermal battery management. High-energy-density batteries generate massive heat impacting performance, service life and safety. Thermal management plays a critical role in preserving battery integrity by regulating overall temperature and localized heat distribution, thus mitigating the risk of thermal runaway. Varies cooling technologies such as air, liquid, and multi-phase material cooling, have been utilized. However, minimizing the maximum temperature while maintaining temperature uniformity remains a critical challenge in battery thermal management. This paper introduces a novel microchannel cooling system with scanning flow for Li-ion batteries. Computational Fluid Dynamics (CFD) models are developed to investigate scanning flow cooling behavior. Parametric study examines the effects of battery numbers, valve switching frequency, and channel numbers on maximum and minimum temperatures, average temperature, and temperature differences. Furthermore, fluid analysis incorporates heat distribution and velocity behavior to study flow characteristics. Experimental analysis validates the cooling capability of the scanning flow method with a 0.17% error rate. The findings highlight scanning flow as an efficient method, enhancing temperature uniformity by 62.5% and reducing the average temperature difference by 92%. This presents a promising avenue for developing effective thermal management solutions for high-energy-density batteries.
Keywords: Cooling; battery; liquid cooling; temperature control